Assessing future availability of water resources in Taiwan based on the Budyko framework. (February 2023) - Lee, Tsung-Yu; Chiu, Chi-Cheng; Chen, Chia-Jeng; Lin, Chuan-Yao; Shiah, Fuh-Kwo
Graphical abstract: Highlights: The Budyko framework was applied to 75 catchments covering a large area of Taiwan. Varied landscape effects determined water resources availability among catchments. Considerable spatial variability in the Budyko-related variables were found. Three clusters were identified based on catchments' movements in the Budyko space. 64 catchments will face the reduced availability of future water resources. Abstract: Assessing water resources availability in a changing climate is a determinant of promoting sustainable development in a region. Such assessment should better be inter-basin in order to unveil a region's overall risk, so a time-varying Budyko framework is developed and adopted in this study. Gauge-based gridded precipitation and temperature, in company with runoff data, were used to derive the Budyko curves for 75 catchments over Taiwan. Downscaled precipitation and temperature data from selected global climate models and Representative Concentration Pathways (RCPs) were then used to calculate the shifts in the Budyko space of each catchment. It was found that the Budyko-related variables (e.g., evaporative and aridity indices, and catchment-specific parameter) exhibited considerable variability island-wide, with a few outliers in certain catchments being modulated by distinct landscape features and/or human activities. Under all RCPs analyzed, the majority of catchments showed the magnified movement vectors pointing at the 1st quadrant in the Budyko space in the late-21st century, suggesting a predominant and aggravating drying trend over Taiwan. Cluster analysis of the movement vectors under RCP8.5, which entailed the least inter-model differences, identified three major clusters, two of which (64 catchments included) indicated a drying trend of varied significancy. According to our findings, without effective mitigation of climate change, an increased likelihood of the worst-case scenario will substantialize the reduced availability of Taiwan's water resources.